Advertisements
Advertisements
Question
Solution
We have,
\[I = \int\frac{\left( 5 x^2 - 1 \right) dx}{x \left( x - 1 \right) \left( x + 1 \right)}\]
\[\text{Let }\frac{5 x^2 - 1}{x \left( x - 1 \right) \left( x + 1 \right)} = \frac{A}{x} + \frac{B}{x - 1} + \frac{C}{x + 1}\]
\[ \Rightarrow \frac{5 x^2 - 1}{x \left( x - 1 \right) \left( x + 1 \right)} = \frac{A \left( x^2 - 1 \right) + Bx \cdot \left( x + 1 \right) + C \cdot x \cdot \left( x - 1 \right)}{x \left( x - 1 \right) \left( x + 1 \right)}\]
\[ \Rightarrow 5 x^2 - 1 = A \left( x^2 - 1 \right) + B \cdot x \left( x + 1 \right) + C \cdot x \cdot \left( x - 1 \right)\]
Putting x = 1
\[ \Rightarrow 5 - 1 = A \times 0 + B \left( 1 \right) \left( 1 + 1 \right) + C \times 0\]
\[ \Rightarrow 4 = B \left( 2 \right)\]
\[ \Rightarrow B = 2\]
Putting x = 0
\[ \Rightarrow 5 \times 0 - 1 = A \left( 0 - 1 \right) + B \times 0 + C \times 0\]
\[ \Rightarrow - 1 = A \left( - 1 \right)\]
\[ \Rightarrow A = 1\]
Putting x + 1 = 0
\[x = - 1\]
\[5 - 1 = A \times 0 + B \times 0 + C \left( - 1 \right) \left( - 2 \right)\]
\[ \Rightarrow C = 2\]
\[ \therefore I = \int\frac{dx}{x} + 2\int\frac{dx}{x - 1} + 2\int\frac{dx}{x + 1}\]
\[ = \log \left| x \right| + 2 \log \left| x - 1 \right| + 2 \log \left| x + 1 \right| + C\]
\[ = \log \left| x \right| + 2 \left\{ \log \left| x^2 - 1 \right| \right\} + C\]
\[ = \log \left| x \left( x^2 - 1 \right)^2 \right| + C\]
APPEARS IN
RELATED QUESTIONS
Integrate the following integrals:
\[\int\text{ cos x cos 2x cos 3x dx}\]
\[\int\frac{1}{2 - 3 \cos 2x} \text{ dx }\]
Evaluate : \[\int\frac{\cos 2x + 2 \sin^2 x}{\cos^2 x}dx\] .
Find : \[\int\frac{e^x}{\left( 2 + e^x \right)\left( 4 + e^{2x} \right)}dx.\]